2009
DOI: 10.1080/00223890902936116
|View full text |Cite
|
Sign up to set email alerts
|

The Interrater Reliability of Elizur's Hostility Systems and Holt's Aggression Variables: A Meta-Analytical Review

Abstract: We provide a meta-analytic review of interrater reliability for scoring the 2 most commonly studied Rorschach (2003) aggression measures: (a) The Elizur (1949) Hostility Scale and its main derivative scoring systems (Holtzman, Thorpe, Swartz, & Herron, 1961; Murstein, 1956) and (b) Holt's (1977, 2005) aggression variables. Substantial reliability was observed for both Elizur's hostility score (e.g., weighted mean summary score correlation = .91, N = 1,279) and Holt's aggression variables (e.g., weighted mean s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Although the Comprehensive System is the dominant approach to the Rorschach, many Rorschach scales were created outside the context of the system. Several reviews have now demonstrated good reliability for nonsystem variables thought to measure aggression (Gacono, Bannatyne-Gacono, Meloy, & Baity, 2005;Katko, Meyer, Mihura, & Bombel, 2009), individuation in relationships , therapy prognosis (Handler & Clemence, 2005), and dependency (Bornstein & Masling, 2005), among others.…”
Section: Reliabilitymentioning
confidence: 99%
“…Although the Comprehensive System is the dominant approach to the Rorschach, many Rorschach scales were created outside the context of the system. Several reviews have now demonstrated good reliability for nonsystem variables thought to measure aggression (Gacono, Bannatyne-Gacono, Meloy, & Baity, 2005;Katko, Meyer, Mihura, & Bombel, 2009), individuation in relationships , therapy prognosis (Handler & Clemence, 2005), and dependency (Bornstein & Masling, 2005), among others.…”
Section: Reliabilitymentioning
confidence: 99%
“…IRR has been analyzed and compared for groups with respect to assessee or rater characteristics in journal peer review [ 35 ], grant peer-review [ 5 , 28 , 36 ], classroom observations of teachers [ 37 – 38 ], university candidates [ 3 ], student ratings, etc. In these areas and others, potential exists for assessee covariates, such as gender and ethnicity, rater characteristics such as rater position, experience or training [ 39 40 ] or covariates of units, e.g. school type or job type, which may moderate IRR and precision of ratings.…”
Section: Discussionmentioning
confidence: 99%